EVALUASI PELAKSANAAN TRI HITA KARANA PADA LINGKUNGAN VILA DI KECAMATAN UBUD - Sanjaya, I Wayan Agus Rene; Suryawan Wiranatha, Agung; Sukewijaya, I Made (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 18 No 1 (2024), 2024)
Development policies in Bali are expected to maintain the sanctity and harmony of Bali nature, according to concept of Tri Hita Karana (THK). Ubud is famous for its unique arts and culture, it is hoped that it will unite in harmony towards harmony based on local wisdom values. Study aims to assess the criteria and analyze the level implementation of THK in the villa environment in Ubud Subdistrict. Determining the location of the research carried out by purposive way. The data collection method was carried out using observation techniques, interviews, questionnaires and literature study. Respondents in this study were villa managers. The three elements of THK include parhyangan, pawongan, and palemahan. The highest score for parhyangan is a indicator: religious activities carried out every day, as well as periodically (odalan) (94.60%: very good). The lowest score is the indicator: the implementation of lectures in the villa environment (60.20%: enough). The highest score for pawongan is a indicator: harmonious relationship between employees and owners (95.00%: very good). The lowest score is a indicator: efforts to increase human resources in the surrounding community (77.20%: good). The highest score for palemahan is a indicator: there is a commitment to the environmental quality of the villa (89.80%: very good). The lowest score is a indicator: waste management and hazardous and toxic materials (B3) (58.40%: enough). The level of implementation of THK in villas in Ubud Subdistrict is 81.91% (good). The level of implementation of THK element is parhyangan at 84.00% (very good), pawongan at 86.28% (very good), and palemahan at 75.44% (good). It is hoped that the THK indicator can continue to be further developed, in a big tourism area and the application of the mandatory Environmental Management Statement is expected to achieve sustainable and environmentally friendly tourism in villas or the tourism industry in Bali. Keywords: Implementation; Tri Hita Karana; Ubud Subdistrict; Villa